Satu Kahkonen and Anthony Lanyi. Institutions, Incentives, and Economic Reforms in India. New Delhi: Sage Publications, 2000. 516 pages. Hardback. Price Indian Rs 595.00. (The Pakistan Development Review, 2001)
The economic reform process began in India in 1991. However, the reform agenda is still far from its goals as is evident from low per capita income. Thus, this reform effort has not produced the desired outcome of a faster rate of economic and social development in a meaningful way. It is the premise of this volume that to transform the social and economic landscape, the proposed reforms should be broadbased and multi-pronged which take into account incentives for the stockholders in both the private and public sectors. The institutions are the rules that govern economy and include the fundamental legal, political, and social rules that establish the basis for production, exchange, and distribution. The two editors of this volume have received contributions from a number of authors and the wide range of papers are grouped under five main headings: political economy of reforms, reforming public goods delivery, reform issues in agriculture and rural governance, and reforming the district and financial sector.